Encyclopedia of the scientific revolution : from Copernicus to Newton - Applebaum, Wilbur (New York : Garland Pub., 2000)
An alphabetical resource on science in the sixteenth and seventeenth centuries, including biographical and conceptual entries with an interdisciplinary emphasis.
Includes bibliographical references and index.
Booklist.
Library Journal.
Wilson's Senior High School.
Adult
Keywords: Science -- Europe -- History -- 16th century -- Encyclopedias; Science -- Europe -- History -- 17th century -- Encyclopedias; Science -- Europe -- History -- Encyclopedias